PERSEPSI WARIS MASYARAKAT TRANSMIGRASI DI KAMPUNG ARSO VII KABUPATEN KEEROM PROPINSI PAPUA PERSPEKTIF HUKUM WARIS ISLAM - Muhamad Zainal Abidin (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2020)
AbstractThis research examines the perception of inheritance law in the transmigration community. Given that in social life, transmigration communities are multicultural, consisting of various ethnic groups and their respective cultural patterns, which come from their place, environment and social conditions of origin. Including the issue of inheritance law in the transmigration area which has its own uniqueness. The purpose of this research is to obtain information related to people's perceptions of inheritance law that applies in accordance with the customs and traditions of society. This study used a descriptive qualitative method, with a sociological approach to the perception of the transmigration community. The results of the research conducted, it can be concluded that the public perception of inheritance, namely assets that are distributed before the heir dies by means of deliberation to obtain consensus which is witnessed by the family and divided by appointment of inheritance to the heirs.Keywords: Inheritance Law; Transmigration Community; Inheritance Perception.